How telepresence and perceived enjoyment mediate the relationship between interaction quality and continuance intention: Evidence from China Zisha-ware Digital Museum - Shi, Mengjie; Deng, Liyuan; Zhang, Mingshan; Long, Yanghuan (PLOS ONE, 2025)
The rapid development of digital technologies and the diversification of user needs have made digital museums significant platforms for cultural dissemination and education, attracting unprecedented attention. This study aims to investigate how interaction quality influences users’ psychological responses and their continuance intention to use digital museums. By integrating the Stimulus-Organism-Response (S-O-R) model and telepresence theory, this study proposes a novel model to examine users’ continuance intention. A questionnaire survey of visitors to the China Zisha-ware Digital Museum (CZDM) yielded 414 valid responses, which were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that: 1) The interaction quality of digital museums (i.e., interactivity, vividness, and authenticity) and users’ psychological responses (i.e., telepresence, perceived enjoyment) significantly affect users’ continuance intention to varying degrees. 2) Telepresence significantly mediates the relationship between interaction quality and continuance intention. 3) Perceived enjoyment serves as an important mediator between interactivity, vividness, and continuance intention, while its mediating role between authenticity and continuance intention is not significant. This study offers theoretical and practical insights for optimizing digital museum user experience design to enhance continuance intention, while also promoting the dissemination of digital culture and supporting educational efforts.